PENELANTARAN NAFKAH SUAMI ATAS ISTRI MENURUT KHI DAN UNDANG-UNDANG NO. 1 TAHUN 1974 - Wiwin Siti Aminah; Tita Muspitawati (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
Islam has given some provisions concerning the obligation of husband and wife in the family, that livelihood becomes the responsibility of the husband to fulfill the basic needs of the family. Mandatory maintenance for husband since marriage contract is done. The obligation to provide for the family (children and wives) is left to men as husbands and husbands, not to wives. If a husband does not want to earn a living when he has the ability, then he has neglected his duty as head of the household. If the wife felt her rights were ignored then in Law Number 1 Year 1974 article 34 paragraph (3), so also in Compilation of Islamic Law (KHI) section 77 paragraph (5) wife can file lawsuit to Court.